ASSESSMENT OF PEATLAND ECOSYSTEM CHARACTERISTICS IN THE PEAT HYDROLOGICAL UNIT OF GONGAN RIVER- NILO RIVER, RIAU PROVINCE: Kajian Karakteristik Ekosistem Gambut pada Kesatuan Hidrologi Gambut Sungai Gongan-Sungai Nilo Provinsi Riau - Budi Susetyo; Waluyo; Erwin Hermawan (Geomatika, 2024)
Minister of Environment and Forestry Regulation No. P.14/MENLHK/SETJEN/KUM.1/2/2017 establishes protocols for assessing and defining the function of peat ecosystems, involving 13 criteria. Among these, survey points must align with map coordinates, with a displacement limit of 200 meters. The research aims to meticulously control the characteristics of peatlands in the Peat Hydrological Unit (PHU) of Gongan River-Nilo River, Riau Province, following the work plan to ensure that observations align with actual conditions. The Haversine method gauges the distance between planned and actual observation points, revealing an average shift of 19.9 meters, ranging from 3.38 to 198.9 meters, indicating surveyor accountability. Field data shows 68% of the area with groundwater levels below 30 cm, and 32% between 30 and 60 cm. Channel water heights are predominantly between 50 and 100 cm (68%), with 22% lower and 10% higher. Soil pH consistently measures below 4 (100%), similar to channel water (73%), and substratum (81%) with most below 4. Only 3.1% of groundwater exceeds 300 μS/cm in electrical conductivity, while 96% are below 300 μS/cm, including low substratum conductivity. Total dissolved solids are mostly below 75 ppm (97%), with 3% between 75 and 150 ppm. The average peat thickness is 367.9 cm, primarily clay/river sediment at the hemic level. It can be concluded that all field survey results in the PHU Gongan-Nilo River can be accepted as valid data that can be used as a basis for development planning/regional determination in this area.